Outpatient dermatology consultations for oncology patients with acute dermatologic adverse events impact anticancer therapy interruption: a retrospective study. (5th February 2020) - Barrios, D.M.; Phillips, G.S.; Freites‐Martinez, A.; Hsu, M.; Ciccolini, K.; Skripnik Lucas, A.; Marchetti, M.A.; Rossi, A.M.; Lee, E.H.; Deng, L.; Markova, A.; Myskowski, P.L.; et al.
Abstract: Background: Dermatologic adverse events (dAEs) of anticancer therapies may negatively impact dosing and quality of life. While therapy interruption patterns due to dAEs have been studied in hospitalized cancer patients, similar outcomes in outpatient oncodermatology are lacking. Objectives: To analyse the therapy interruption patterns, clinico‐histopathologic characteristics and management outcomes of outpatient dermatology consultations for acute dAEs attributed to the most frequently interrupted class of oncologic agents. Methods: We performed a retrospective cohort study of all cancer patients who received a same‐day outpatient dermatology consultation for acute dAEs at our institution from 1 January to 30 June 2015. Relevant data were abstracted from electronic medical records, including demographics, oncologic history and explicit recommendations by both the referring clinician and consulting dermatologist on anticancer therapy interruption. Consultations with the most frequently interrupted class of oncologic treatment were characterized according to clinico‐histopathologic features, dermatologic management and clinical outcomes. Results: There were 426 same‐day outpatient dermatology consultations (median age 59, 60% female, 30% breast cancer), of which 295 (69%) had systemic anticancer therapy administered within 30 days prior. There was weak inter‐rater agreement between referring clinicians and consulting dermatologists on interruption of anticancer treatment ( n = 150, κ = 0.096; 95% CI −0.02 to 0.21). Seventy‐three (25%) consultations involved interruption by the referring clinician, most commonly targeted therapy (24, 33%). Maculopapular rash was commonly observed in 23 consultations with 25 dAEs attributed to targeted agents (48%), and topical corticosteroids were most frequently utilized for management (22, 38%). The majority (83%) of consultations with targeted therapy‐induced dAEs responded to dermatologic treatment and 84% resumed oncologic therapy, although three (19%) at a reduced dose. Rash recurred only in two instances (13%). Conclusions: A high frequency of positive outcomes in the management of targeted therapy‐induced dAEs by outpatient consulting dermatologists and low recurrence of skin toxicity suggests impactful reductions in interruption of anticancer therapy.